Two new species of Glyphocrangon (Decapoda: Caridea: Glyphocrangonidae) from the East China Sea and the Philippines - Han, Qingxi; Li, Xinzheng (Zootaxa, 2014)
The present paper reports two new species of Glyphocrangon (Crustacea, Caridea, Glyphocrangonidae) collected respectively from the East China Sea and the Philippines. G. singularis sp. nov., from the East China Sea, is similar to G. fimbriata Komai & Takeuchi, 1994 with the presence of fringe of setae on dactyl of the third to fifth pereopods, but differs from G. fimbriata by the rostrum shape and the armature on the carapace; G. denticulata sp. nov., from the Philippines, is similar to G. pugnax De Man, 1918 with the entire anterior third carina, but differs from G. pugnax by armatures of the antennal scaphocerite and carapace, the lengths of rostrum and the spines of fifth abdominal somite, and the colouration of carapace.